Sauropodomorph evolution across the Triassic–Jurassic boundary: body size, locomotion, and their influence on morphological disparity - Cecilia Apaldetti (Nature Portfolio, 2021)
Abstract Sauropodomorph dinosaurs were the dominant medium to large-sized herbivores of most Mesozoic continental ecosystems, being characterized by their long necks and reaching a size unparalleled by other terrestrial animals (> 60 tonnes). Our study of morphological disparity across the entire skeleton shows that during the Late Triassic the oldest known sauropodomorphs occupied a small region of morphospace, subsequently diversifying both taxonomically and ecologically, and shifting to a different and broader region of the morphospace. After the Triassic–Jurassic boundary event, there are no substancial changes in sauropodomorph morphospace occupation. Almost all Jurassic sauropodomorph clades stem from ghost lineages that cross the Triassic–Jurassic boundary, indicating that variations after the extinction were more related to changes of pre-existing lineages (massospondylids, non-gravisaurian sauropodiforms) rather than the emergence of distinct clades or body plans. Modifications in the locomotion (bipedal to quadrupedal) and the successive increase in body mass seem to be the main attributes driving sauropodomorph morphospace distribution during the Late Triassic and earliest Jurassic. The extinction of all non-sauropod sauropodomorphs by the Toarcian and the subsequent diversification of gravisaurian sauropods represent a second expansion of the sauropodomorph morphospace, representing the onset of the flourishing of these megaherbivores that subsequently dominated in Middle and Late Jurassic terrestrial assemblages.